Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557289
|View full text |Cite
|
Sign up to set email alerts
|

Smart flashlight

Abstract: While mobile phones affect our behavior and tend to separate us from our physical environment, our environment could instead become a responsive part of the information domain. For navigation using a map while cycling in an urban environment, we studied two alternative solutions: smartphone display and projection on the road. This paper firstly demonstrates by proof-of-concept a GPS-based map navigation using a bike-mounted projector. Secondly, it implements a prototype using both a projector and a smartphone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…A separate theme emerged from discussion of brutal play more generally as a form of play and source of enjoyment. 60 of a total 771 units are described by this theme, divided into three categories: Violence / aggression (44), domination (10), self-restraint (6 Participants suggested that a lot of the enjoyment of brutal games comes from the opportunity to physically dominate other players (see e.g. Figure 8) Our interviews suggest that the enjoyment of brute force games comes not only from the rare opportunity to feel and use your own strength, but also from a sense of competition and opportunity to dominate other players physically.…”
Section: T4: Physical Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate theme emerged from discussion of brutal play more generally as a form of play and source of enjoyment. 60 of a total 771 units are described by this theme, divided into three categories: Violence / aggression (44), domination (10), self-restraint (6 Participants suggested that a lot of the enjoyment of brutal games comes from the opportunity to physically dominate other players (see e.g. Figure 8) Our interviews suggest that the enjoyment of brute force games comes not only from the rare opportunity to feel and use your own strength, but also from a sense of competition and opportunity to dominate other players physically.…”
Section: T4: Physical Awarenessmentioning
confidence: 99%
“…We may also take inspiration from wider HCI work on split attention while performing complex physical movements such as cycling [14,24]. For example we could utilise space to make displays where people may be looking by projecting information on floor or multiple walls [6] (T1:Space).…”
Section: Tune Attentional Demands Of System To Those Of Physical Intementioning
confidence: 99%
“…Using Vibrobelt led to fewer navigation errors than a smartphone mounted on the handlebars. Another approach to navigation used street surface for display as in Smart Flashlight [7]. Matviienko et al [28] found that auditory feedback was preferred by child cyclists.…”
Section: Interaction For Cyclistsmentioning
confidence: 99%
“…Projection can be used as means to provide people with geographic information, even in a mobile context [18,19]. It can be used instead of a screen when it is not inconvenient to look at the device or hold it, as has been demonstrated for instance in a projected bike navigation system [12]. We believe that the potential to support map exploration and navigation through projection has not yet been fully explored.…”
Section: Projected Geographic Mapsmentioning
confidence: 99%